Booth & Hyland, Eds., The Practice Of University History Teaching - Berg, Timothy (Teaching History: A Journal of Methods, 2004)
Practicing historians and teachers are all too aware of the primacy placed on research over teaching by many in the academy. Research is the "serious" work of historians, teaching something merely to be tolerated. Although that’s a pervasive attitude, readers of this journal undoubtedly will scoff at such a distinction, knowing all too well the importance that both activities play in the historical profession. But recognizing the false dichotomy of choosing research or teaching as the more important of our duties doesn’t undercut the reality that scholarship on teaching history is not regarded with the same respect as "content" research.